CULTIVATION OF CORINDER IN SUCCESSION OF THE LETTUCE CULTURE - Linhares, Paulo César Ferreira; Soares Pereira, Maria Francisca; Maracajá, Patrício Borges; Sousa, José da Silva; Sousa, Luci Cleide Farias Soares (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2011)
The use of natural resources disposable in the farm producers it is important to obtain income, and in Brazil northeast region it has been found different spontaneous species as sources of nutrients in the caatinga biome to be used as green manure. This work was conducted at the experimental farm Rafael Fernandes of the Department of Plant Sciences, Federal Rural University of the Semi-Arid (UFERSA), Mossoro, RN, from January to February 2010 with the purpose of to evaluate the cultivation of coriander in succession lettuce. The experimental design was randomized complete block with treatments arranged in 4 x 4 factorial design with three replications, with 144 plants per plot, the first factor consists of the amounts of jitirana (5.4, 8.8 12, 2 and 15.6 t ha-1 on a dry basis), the second time by its incorporation into the soil (0, 10, 20 and 30 days before sowing - DAS). The cultivar of coriander planted was Verdão. The evaluated characteristics were: height and number of stems per plant, fresh and dry mass of shoots. It was observed a significant interaction for number of stems per plant and yield. The best agronomic performance of the coriander was obtained in the amount of 8.02 t ha-1 t ha-1 of silk-flower incorporated into the soil at the time of 30 days. For each ton of flower is incorporated into the soil dry silk observed an average yield of coriander in the order of 395 kg ha-1.